2019
DOI: 10.1182/blood.2019000396
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 dysregulation originates in dendritic cells and mediates graft-versus-host disease via classical signaling

Abstract: Key Points DCs are the principal source of IL-6 dysregulation after alloSCT. IL-6–dependent GVHD is driven by classical signaling of IL-6R on donor T cells but is regulated by trans signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 73 publications
2
25
0
1
Order By: Relevance
“…IL-10, for example, has been shown to mitigate GvHD, 54,70,71 while IL1-β and IL-6 have been shown to enhance GvHD. 56,72 Interestingly, in a purely in vitro study, BEN has been shown to increase IL-10 production by a B-cell cancer line. 73 This makes the cytokine profile following BEN administration an interesting candidate for further investigation of the mechanism by which BEN is reducing GvHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10, for example, has been shown to mitigate GvHD, 54,70,71 while IL1-β and IL-6 have been shown to enhance GvHD. 56,72 Interestingly, in a purely in vitro study, BEN has been shown to increase IL-10 production by a B-cell cancer line. 73 This makes the cytokine profile following BEN administration an interesting candidate for further investigation of the mechanism by which BEN is reducing GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical roles of cytokine milieu 54,55 and host antigen presenting cells [56][57][58] in the pathophysiology of GvHD, we evaluated the effect of each on T-cell phenotype. On day 0, we collected plasma (Supplemental Figure 6a) and isolated splenic pan-DCs (Supplemental Figure 6b-D) from BEN-TBI and CY-TBI conditioned mice.…”
Section: Ben-tbi Conditioning Improves Gvhd Independently Of Donor Tregsmentioning
confidence: 99%
“…Meanwhile, IL-6Rα can be proteolytically shed and bind to IL-6 as a soluble receptor (sIL-6Rα) and associate with gp130 on target cells in the transsignaling [18]. However, in IL-6 cluster signaling, the IL-6/IL-6Rα complex forms internally in dendritic cells (DCs) and interacts with gp130 expressed on antigen-specific T cells, a pathway which may be relevant to multiple T lymphocyteassociated autoimmune diseases (see Figure 2) [19]. After [22].…”
Section: Interleukin -6mentioning
confidence: 99%
“…NK cells were shown to mediate tumor regression in AML patients, eliminate graft rejection and protect patients against GvHD (51,52). The presence of mature antigen-presenting dendritic cells (DCs) has been correlated with improved survival (53)(54)(55)(56). T regulatory (Treg) cells down-modulate T-cell activation through the production of immunosuppressive cytokines (TGFβ, IL-10), as well as through surface receptors (CTLA4), and can drastically impact both the anti-tumor immune response as well as the control of GvHD (57)(58)(59).…”
Section: Monitoring Immune Cell Reconstitutionmentioning
confidence: 99%